Polymerisation-induced self-assembly (PISA) as a straightforward formulation strategy for stimuli-responsive drug delivery systems and biomaterials: recent advances. (12th November 2020) - Phan, Hien; Taresco, Vincenzo; Penelle, Jacques; Couturaud, Benoit
Abstract : Stimuli-responsive amphiphilic block copolymers obtained by PISA have emerged as promising nanocarriers for enhancing site-specific and on-demand drug release in response to a range of stimuli such as pH, redox agents, light or temperature. Abstract : Stimuli-responsive amphiphilic block copolymers have emerged as promising nanocarriers for enhancing site-specific and on-demand drug release in response to a range of stimuli such as pH, the presence of redox agents, and temperature. The formulation of amphiphilic block copolymers into polymeric drug-loaded nanoparticles is typically achieved by various methods ( e.g. oil-in-water emulsion solvent evaporation, solid dispersion, microphase separation, dialysis or microfluidic separation). Despite much progress that has been made, there remain many challenges to overcome to produce reliable polymeric systems. The main drawbacks of the above methods are that they produce very low solid contents (<1 wt%) and involve multiple-step procedures, thus limiting their scope. Recently, a new self-assembly methodology, polymerisation-induced self-assembly (PISA), has shown great promise in the production of polymer-derived particles using a straightforward one-pot approach, whilst facilitating high yield, scalability, and cost-effectiveness for pharmaceutical industry protocols. We therefore focus this review primarily on the most recent studies involved in the design and preparation of PISA-generated nano-objects which are responsive to specific stimuli, thus providing insight into how PISA may become an effective formulation strategy for the preparation of precisely tailored drug delivery systems and biomaterials, while some of the current challenges and limitations are also critically discussed.